STATE AID SCHEMES FOR SMALL-SCALE AGRICULTURE IN POLAND UNDER RURAL DEVELOPMENT PROGRAMME FOR YEARS 2014-2020 - Jakub GOŁAŚ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The main aim of the article was to present basic data concerning the issue of state aid schemes for small-scale agriculture in Poland under current Rural Development Programme for the period 2014-2020. The research concerns such issues as: definition of small farms, structure of agricultural holdings in Poland by area group of agricultural land and economic size classes or basic state aid schemes designed for small-scale agriculture. Firstly, it should be highlighted here that there is no uniform definition of small farms under Polish legal system and different researchers propose various definitions. In terms of structural issues, it should be noted that smaller agricultural holdings are dominant group of farms in Poland. Such regularity may be also observed in case of economic size classes, where majority of farms represented lower economic size classes. Finally, it is worth noting that the State offers various aid schemes that are designed to foster, promote and stimulate development of small-scale agriculture in Poland.